Contro interno aduanero y su relacion con el alto indice del contrabando en colombia (2023)
The present investigation entitled "THE CUSTOMS INTERNAL CONTROL AND ITS CONNECTION WITH THE HIGH SMUGGLING RATE IN COLOMBIA", will try to contribute to the problem in the fight against the high levels of smuggling that the country has been going through for years and that places it in the 91st place out of 180 in the scale of countries with the most transparent perception index, by studying the internal control of the customs offices and all its processes and regulations; The above is in order to find or discover any inaccuracies or weaknesses in customs that may be promoting this situation. The research topic will delve into the impact that the above mentioned problems have in the country and the inaccuracies that may have the internal control and risk control that is carried out in customs; in turn, it seeks to find a connection between the above mentioned and the high rate of smuggling throughout the Colombian territory, wanting to make proposals for improvement and reduce unfair competition in the market. This documentary research intends to encourage good practices and the correct way of importing or exporting merchandise from outside the country legally and without the intention of evading or persuading customs taxes, significantly affecting the Colombian economy.